Impact of sensible storage material and copper fins on the performance of serpentine tube type vacuum tube collector system: Energy, technical and financial assessment - Chopra K.; Kumar A.; Kumar Pathak S.; Tyagi V.V.; Pandey A.K.; Mansor M. (Elsevier Ltd, 2025)
This paper offers an experimental evaluation of an SR-EVTC (serpentine evacuated tube collector) system embedded with a copper annular fin and sensible heat storage liquid (SR-EVTC/SS-AF). In this study developed system was compared with the control EVTC (SR-EVTC/CS) under the same meteorological conditions. In addition, the technical and financial feasibility of SR-EVTC/SS-AF and SR-EVTC/CS in different locations of India was also assessed for their practical implementation and commercial viability. To determine their thermal performance, the developed systems were investigated during sunny and cloudy days for three different water flow ranges, i.e. 0.008, 0.012, and 0.016 m3/h. During the experimental investigation on clear sunny days, both SR-EVTC/SS-AF and SR-EVTC/CS were found to have the highest daily average energy efficiency of 82.45 % and 63.88 %, respectively, when the flow rate was 0.016 m3/h. Whereas during cloudy days, the highest value of daily energy efficiency was achieved to be 87.78 % and 74.35 % respectively for EVTC/SS and EVTC/WSS, when the flow rate was 0.008 m3/h. It has been noticed that on average, the same amount of solar radiation is incident at Location-I and Location-V. However, due to the lowest ambient temperature, the annual energy demand at Location-V is found to be the highest. For SR-EVTC/SS-AF, values of PBP and LCSWH are found to be lowest for Location-I due to the lowest ratio of annual energy requirement to average the annual solar irradiation incident, whereas the value of NPW is highest for Location-V due to the highest annual energy demand. ? 2024 Elsevier Ltd